Apoptose no carcinoma de próstata - Fermozelli, Ricardo Abeche [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Prostate carcinoma is a frequent cause of morbidity and mortality in Western populations, with high frequency in Brazil. It is the most common cancer among men and the second leading cause of death, preceded by lung cancer. Its incidence has increased continuously in recent decades due to increased life expectancy and the western lifestyle. Apoptosis is a cell death mechanism that occurs in many physiological processes. It is known that tumors show progressive resistance to apoptosis. It is regulated by caspases, apoptosis effector enzymes, whose activation is strictly controlled by Innibitors of Apoptosis Proteins, IAPs, which in turn are modulated by IAP activity inhibitory molecules, with SMAC/Diablo being the main one and the most studied. We studied the relationship between IAPs (XIAP and Survivin) and SMAC in prostatic carcinomas and its correlation with the Apoptotic Index (AI), cellular proliferation, immunohistochemistry expression of protein p53 and patient survival rate. TMA paraffin blocks were made with prostate cancer tissue from patients operated at the Clinics Hospital, Botucatu School of Medicine, from 1980 to 2000. These were submitted to immunohistochemical reaction to Survivin, XIAP, SMAC, p53, cleaved Caspase 3 (apoptotic index) and Ki67 (cell proliferation index). The slides were read by two pathologists, wich graduated the intensity and percentage of positive cells according to immuno-expression of each marker. These results were correlated with the Gleason grade, prognostic categories (ISUP) and patient survival data. A correlation was verified between tumor differentiation and the cell proliferation rate. The intensity of p53 reaction was also associated with the degree of neoplastic differentiation. Patient survival was higher in cases with lower ki67 labelling and lower Gleason and Prognostic Categories grading

O Carcinoma de Próstata é frequente causa de morbi-mortalidade nas populações ocidentais, tendo alta frequência no Brasil. É a neoplasia mais comum do homem, e a segunda causa de óbito, precedido pelo câncer de pulmão. Sua incidência vem aumentando continuamente nas últimas décadas devido ao aumento da perspectiva de vida e ao estilo de vida ocidental. A apoptose é mecanismo de morte celular que ocorre em diversos processos fisiológicos. Sabe-se que neoplasias tem progressiva resistência à apoptose. Esta é regulada pelas caspases, enzimas efetoras da apoptose, cuja ativação é rigorosamente controlada pelas proteínas inibidoras da apoptose, as IAPs, que por sua vez tem atividade modulada por moléculas inibidoras de IAPs, sendo a SMAC/Diablo a principal e a mais estudada. Neste trabalho estudamos a relação entre as IAPs e SMAC nos carcinomas prostáticos e sua correlação com o Índice Apoptótico (IA), proliferação celular, imuno-expressão da proteína p53 e taxa de sobrevida dos pacientes. Foram confeccionados blocos de parafina de TMA com tecido de câncer prostático de pacientes operados no Hospital das Clinicas da Faculdade de Medicina de Botucatu de 1980 a 2000. Estes foram submetidos à reação imuno-histoquímica para Survivina, XIAP, SMAC, p53, Caspase 3 Clivada (índice apoptótico) e Ki67 (índice de proliferação celular). As laminas foram lidas por dois patologistas, sendo obtidas graduações de intensidade de imuno-expressão e/ou percentuais de positividade celular. Esses resultados foram correlacionados com a graduação de Gleason, categorias prognósticas (ISUP) e dados de sobrevida dos pacientes. Houve correlação entre a diferenciação da neoplasia e o índice de proliferação celular. A intensidade da marcação para p53 também esteve associada ao grau de diferenciação neoplásica. A sobrevida dos pacientes foi maior nos casos com menor ki67 e menores Gleason e Categorias Prognósticas
Keywords: Apoptose; Próstata - Câncer; Proteínas - Inibidores; Prognostico; Apoptosis